Infection of Cyclospora cayetanensis in children under 15 years of age in Kathmandu valley - Paudyal, Rabin; Tandukar, Sarmila; Sherchand, Ojaswee; Amatya, Jyoti; Sherchand, Jeevan B (Scientific World, 2011)
Cyclospora cayetanensis is a rapidly emerging pathogen in developing countries like Nepal. It causes persistent diarrhea in children and in immunocompromised individuals. The study was carried out in children less than 15 years of age in Kathmandu Valley. A total of 302 stool samples were collected from different Sukumbasi (Slum children) areas of Kathmandu Valley. The samples were observed microscopically using normal saline and potassium dichromate preparation and the test was further confirmed by Sheather’s sucrose flotation and Kinoyoun’s modified acid fast staining technique. Out of the total sample processed C. cayetanensis oocysts were found in 24 (7.94 %) cases. The oocyst were distributed more in children of age group 3-6 years which constituted 5.49% of the total cases ( ÷2=69.15 p: 0.001) and distributed more in months of June (8) and July (8) (÷2=9.042 p: 0.250) whereas abdominal pain was the most common symptoms in infected children. These findings indicate that C. cayetanensis is rapidly emerging enteropathogen in children. So, active surveillance should be continued among diarrhea patients to look for different C. cayetanensis infection and to define the shifting patterns in the seasonal variations of this parasite. Key words: Cyclospora cayetanensis; Diarrhea; Children; Faecal specimen DOI: http://dx.doi.org/10.3126/sw.v9i9.5525 SW 2011; 9(9): 86-89